The study of the perception of diabetes mellitus among the people of Petaling Jaya in Malaysia - Iqbal, Mohsena; Yasmin, Farzana; Haque, A. K. M. Ahasanul; Rashid, Mohammad Abdur; Kohinoor, Pervin; Hasan Maziz, Mohammad Nazmul (Universidad Técnica de Manabí (UTM), 2022)
Diabetes mellitus is a worldwide medical problem with lack of knowledge, high costs, and maximum cause of mortality. The assessment of knowledge is very important about diabetes mellitus and its causes, symptoms, complications, risk factors among the general population in Petaling Jaya due to gradual increase in diabetes and its complications among patients. Therefore, this study was conducted to analyze the perception of diabetes mellitus among the people residing in Petaling Jaya, Selangor, Malaysia. This is descriptive cross-sectional study which included 400 samples of various ages, sexes, ethnicities, income levels, education levels and family history of diabetic patients from ten policlinics in Petaling Jaya, Malaysia. A validated questionnaire with five elements was used for this study. The collected data from the respective respondents were analyzed through SPSS software. SPSS has been used to analyse the demographic profile of the respondents, as well as perform exploratory factor analysis and multiple regression analysis. The study's findings indicated that general knowledge of diabetes mellitus, knowledge of risk factors of diabetes, knowledge of symptom of diabetes mellitus, knowledge of complications of diabetes mellitus are factors that significantly affect perception of diabetes mellitus among the people residing in Petaling Jaya, Selangor, Malaysia.